Estudos morfológicos, histoquímicos e ultraestruturais do tubo digestivo de três espécies do gênero Leporinus (Characiformes, Anostomidae) - Chedid, Renata Alari [UNESP] (2016)
This work described the digestive tube of Leporinus elongatus, L. macrocephalus and L. obtusidens by anatomic, hislogical, histochemical and ultrastructural studies. Fragments of esophagus, stomach, and intestine were destined to morphological, histochemical and cytochemistry routines. The structure of the digestive tube of the three species studied were composed by short esophagus, Y-shaped caecal stomach and coiled intestine with circular folds related to an increase in time of food passage. Pyloric caeca were observed in the anterior intestine associated with digestion and a increase of absorption surface. The esophagus presented a stratified squamous epithelium, composed by ephitelial cells and goblet cells. The epithelial cells turned to the esophageal lumen presented fingerprint-like microridges in the apical plasmatic membrane associated to the protection and Anchorage of mucosubstances. The goblet cells presented cytoplasm filled with secretion granules showing different eletrodensities. The granules were composed of neutral and acidic mucosubstances in different instensities dependind of the organ region observed and specie studed. In L. macrocephalus were found taste buds in the anterior region of esophagus, important for taste and food selection. The stomach was divided in glandular cardic and fundic regions and aglandular pyloric region with the presence of pyloric sphincter. The gastric lining epithelium was identified as columnar simple with neutral apical mucosubstances related to musoca protection against gastric acids. The instestine presented simple columnar epithelium composed mainly for enterocytes with apical microridges that decreased in height in the posterior direction and goblet cells that increased in number toward the rectum. The enzyme alkaline phosphatase was observed in the brush border with higher intensity in the anterior intestine. The goblet cells showed neutral and acidic secretion granules important ...